Kingdom of the Netherlands : Aruba. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation highlights that Aruba's economic recovery continues, although at a slowing pace. The authorities have managed well the impact of the crisis in Venezuela through diversification of product markets and tourism sources. Nonetheless, a deepening of the crisis is a downside risk-mainly through a potentially sizable influx of immigrants and refugees. It is recommended to identify additional reform measures to achieve Aruba's fiscal targets. These measures should involve a mix of revenue increases and expenditure restraint, and be prioritized, sequenced, equitable, and well-communicated to minimize implementation risks and ensure the measures' durability. The government devised a reform agenda with fiscal consolidation as a key pillar. Additional measures are needed to achieve the authorities' fiscal targets. The additional adjustment should contain a mix of tax reforms and expenditure rationalization. The fiscal measures in 2019 are expected to deliver a large upfront increase in revenues but it will be important to strike a balance between revenue increases and expenditure restraint in subsequent years.